Internal iliac coverage during endovascular repair of abdominal aortic aneurysms is a safe option: A preliminary study. (February 2017) - Kansal, Vinay; Jetty, Prasad; Kubelik, Dalibor; Hajjar, George; Hill, Andrew; Brandys, Tim; Nagpal, Sudhir
Endovascular aneurysm repairs lacking suitable common iliac artery landing zones occasionally require graft limb extension into the external iliac artery, covering the internal iliac artery origin. The purpose of this study was to assess incidence of type II endoleak following simple coverage of internal iliac artery without embolization during endovascular aneurysm repair. Three hundred eighty-nine endovascular aneurysm repairs performed by a single surgeon (2004–2015) were reviewed. Twenty-seven patients underwent simple internal iliac artery coverage. Type II endoleak was assessed from operative reports and follow-up computed tomography imaging. No patient suffered type II endoleak from a covered internal iliac artery in post-operative computed tomography scans. Follow-up ranged from 0.5 to 9 years. No severe pelvic ischemic complications were observed. In conclusion, for selected cases internal iliac artery coverage without embolization is a safe alternative to embolization in endovascular aneurysm repairs, where the graft must be extended into the external iliac artery.